Two‐faced haemophagocytic lymphohistiocytosis: comparative review of two cases of adult haemophagocytic lymphohistiocytosis. Issue 2 (February 2014) - Mayson, E.; Saverimuttu, J.; Warburton, P.
Abstract Haemophagocytic lymphohistiocytosis (HLH) is a rare but potentially fatal disease of children and adults. Cytokine dysfunction, uncontrolled accumulation of activated T‐cells and histiocytes, and the inability to terminate the immune response lead to the clinical manifestations of extreme inflammation and end‐organ damage. HLH is notoriously underreported because of its ability to mimic many other common diseases. Here, we outline two cases of HLH, one primary and the other secondary, to highlight some of the differences and to discuss therapeutic principles and emerging concepts.